2005
DOI: 10.1074/jbc.m413609200
|View full text |Cite
|
Sign up to set email alerts
|

The Mouse Cell Surface Protein TOSO Regulates Fas/Fas Ligand-induced Apoptosis through Its Binding to Fas-associated Death Domain

Abstract: Mouse TOSO, the homologue of human TOSO gene, was cloned and characterized in the present study. Using immunofluorescence confocal microscopy we localized TOSO to the cytoplasmic membrane of expressing cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 32 publications
2
22
2
Order By: Relevance
“…Together with the antiapoptotic effects of Toso in type I and type II cells, these data suggest that Toso generally exhibits a protective function on death receptor-mediated forms of cell death. In addition, unlike earlier reports on type II Jurkat cells, 10,19 we observed no significant increase in caspase-8 cleavage in BJAB (type I) Toso knock-down cells, although these cells exhibit enhanced apoptosis on CD95 stimulation compared with control cells (supplemental Figure 4C). Together, our results indicate that Toso exhibits its antiapoptotic function by acting on signaling events that either lie downstream or in parallel to the activation of initiator caspase-8.…”
Section: Toso Is a Novel Negative Regulator For Cd95-induced Apoptosiscontrasting
confidence: 99%
See 1 more Smart Citation
“…Together with the antiapoptotic effects of Toso in type I and type II cells, these data suggest that Toso generally exhibits a protective function on death receptor-mediated forms of cell death. In addition, unlike earlier reports on type II Jurkat cells, 10,19 we observed no significant increase in caspase-8 cleavage in BJAB (type I) Toso knock-down cells, although these cells exhibit enhanced apoptosis on CD95 stimulation compared with control cells (supplemental Figure 4C). Together, our results indicate that Toso exhibits its antiapoptotic function by acting on signaling events that either lie downstream or in parallel to the activation of initiator caspase-8.…”
Section: Toso Is a Novel Negative Regulator For Cd95-induced Apoptosiscontrasting
confidence: 99%
“…This observation extends previous reports describing an interaction between the death domain of RIP1 and FADD, 29 and an in vitro interaction between FADD and the C-terminus of Toso. 19 While Toso and RIP1 interact constitutively with each other, the association of FADD with the complex is stabilized by CD95-stimulation. Furthermore, our studies using the RIP1-K377R ubiquitination mutant indicate that efficient recruitment of FADD also depends on RIP1 ubiquitination.…”
Section: Toso Facilitates Rip1 Ubiquitinationmentioning
confidence: 99%
“…In Jurkat cells stably transfected with TOSO, it was demonstrated that Fas-induced activation of caspase-8 was significantly inhibited by the expression of TOSO. 9 In addition to that, it was shown in CLL cells that PI3-kinase enables their survival by preventing caspase-8 activation. 14 Furthermore, recent results suggest that caspase-8 processing is inhibited by TOSO through up-regulation of cFLIP.…”
Section: Discussionmentioning
confidence: 96%
“…Besides protection of CLL cells from Fas-induced apoptosis, it was also elucidated that TOSO counteracts TNF-induced apoptosis. 9 In CLL cells, 2 related members of the TNF family, that is, BAFF (B-cell activating factor of the TNF family) and APRIL (a proliferation-inducing ligand) were shown to be overexpressed and involved in resistance to apoptosis through an autocrine pathway. 15 In our experiments, we could demonstrate that CLL cells down-regulate TOSO after being stimulated via their CD40 receptor by CD40L.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation